La scuola e le sfide della complessità - Ceruti, Mauro (Studi sulla Formazione/Open Journal of Education, 2017)
The fragmentation of knowledge, information and experience is a major obstacle to formulating and understanding the problems. Therefore, integrating what is frag-mented is an unavoidable educational challenge. Pursuing the integration of knowledge and experience is a main cultural challenge for school education. The aim is to foster a complex, multi-dimensional knowledge, which is appropriate to deal with the complexity and multi-dimensionality of objects of knowledge and problems characterizing the new global human condition.